Adaptive social protection in Indonesia – Stress-testing the effect of a natural disaster on poverty and vulnerability - Katrin Gasior; Gemma Wright; Helen Barnes; Michael Noble (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
Indonesia is among the countries with the highest exposure to natural disasters, and risks are expected to increase in the future due to climate change. Natural disasters and also other shocks require well-developed social protection systems that are able to cushion the economic consequences for those most vulnerable to these events. Many international and national organisations advocate for 'Adaptive Social Protection' (ASP) which links social policy with strategies on disaster risk reduction and climate change adaptation. The main emphasis is on improving households' ability to prepare for, cope with, and adapt to shocks. This paper uses the tax-benefit microsimulation model INDOMOD to analyse the adaptiveness of the Indonesian social protection system both under normal conditions, and after a simulated hypothetical income shock caused by a natural disaster, using El Ni\~no as a showcase. El Ni\~no is a climate phenomenon that has the ability to change the global atmospheric circulation and as such to influence temperature and precipitation around the world. The drought caused in severely hit regions in Indonesia leads to a disruption of established crop patterns and harvest losses. The dry periods furthermore often cause forest fires affecting the livelihood of those employed in the forestry, transportation, tourism, and public health sector. The analysis focuses first on how the current tax-benefit system prepares individuals and households for a shock (Section 6.1). Secondly, it tests whether the level of preparedness improves after introducing a hypothetical policy reform by augmenting existing benefits and by introducing two new categorical benefits for old-age and disabled individuals ('augmented reform') (Section 6.2). Next, the analysis stress-tests the welfare system by introducing an income shock caused by a hypothetical El Nino event. Based on information from previous events, we simulate a labour market income shock to individuals living in regions more likely to be significantly hit and working in sectors affected by such an event. The analysis explores the impact of the income shock under the current tax-benefit system, under the augmented hypothetical reform and under an additional hypothetical reform that introduces emergency benefits in addition to the existing policy design ('reactive reform') (Section 6.3).
Keywords: 330; Income Dynamics; Geography; Welfare Benefits; Taxation; Poverty; Microsimulation; Social Policy; Households